Improved PID controller based on piecewise affine function in data driven control framework - Mohd Ikhmil Fadzrizan, Mohd Hanif (2022)
In recent years, with the rapid developments of science and technology, practical applications in various fields such as chemical, machinery, electronics and electricity industries have caused the process to become more complex. This subsequently causes the modelling of the plant using first principles or system identification to become more difficult. In general, the PID controller has been successfully applied in various applications. However, the PID gains which are proportional (